Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/toxsci/kfab112
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir Impairs Stem Cell-Based 3D Morphogenesis Models in a Manner Dependent on Dose and Timing of Exposure: An Implication for Its Developmental Toxicity

Abstract: Dolutegravir is an anti-retroviral drug of the integrase strand transfer inhibitor class used to treat HIV infection. It is the recommended first-line regimen for most people, including women of childbearing age. However, some human and animal studies have suggested that dolutegravir causes birth defects, although its developmental toxicity remains controversial. Here, we investigated the adverse effects of dolutegravir using pluripotent stem cell-based in vitro morphogenesis models that have previously been v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Thus, usage of a DTG-based regimen by most pregnant women LWHIV or those of child-bearing age worldwide will be inevitable. With the recurring acknowledgment from clinical and basic science research about potential associations of DTG with neurodevelopmental toxicity ( Zash et al, 2018a ; Cabrera et al, 2019 ; Zash et al, 2019 ; Crowell et al, 2020 ; Mohan et al, 2020 ; Bade et al, 2021 ; Kirkwood-Johnson et al, 2021 ; Tukeman et al, 2023 ), the development of novel therapeutic interventions to maximize therapeutic gains of highly efficacious DTG while limiting adverse effects during pregnancy is timely. Recently, clinical usage of LA-CAB for treatment and prevention therapies ( U S Food and Drug Administration FDA, 2021a ; U S Food and Drug Administration FDA, 2021b ) has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, usage of a DTG-based regimen by most pregnant women LWHIV or those of child-bearing age worldwide will be inevitable. With the recurring acknowledgment from clinical and basic science research about potential associations of DTG with neurodevelopmental toxicity ( Zash et al, 2018a ; Cabrera et al, 2019 ; Zash et al, 2019 ; Crowell et al, 2020 ; Mohan et al, 2020 ; Bade et al, 2021 ; Kirkwood-Johnson et al, 2021 ; Tukeman et al, 2023 ), the development of novel therapeutic interventions to maximize therapeutic gains of highly efficacious DTG while limiting adverse effects during pregnancy is timely. Recently, clinical usage of LA-CAB for treatment and prevention therapies ( U S Food and Drug Administration FDA, 2021a ; U S Food and Drug Administration FDA, 2021b ) has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…The functional characteristics and PCR primer sequences of the mouse genes examined are listed in Table 1 . Previous studies have shown that the expressions of these genes are dysregulated by various chemical exposures that impair the morphogenesis of mouse MEBs (Kim & Marikawa, 2018 ; Kirkwood‐Johnson et al, 2021 ; Lau & Marikawa, 2014 ; Li & Marikawa, 2015 , 2016 , 2020 ; Warkus & Marikawa, 2018 ; Yuan & Marikawa, 2017 ), and that the presence of morphological impairment in mouse MEBs correlates with the in vivo developmental toxicity of chemical exposures with a concordance of 82.9% (Warkus & Marikawa, 2017 ). The characteristics and PCR primer sequences of the human genes are described in the previous study (Marikawa et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics and PCR primer sequences of the human genes are described in the previous study (Marikawa et al, 2020 ). The procedures for RNA extraction, cDNA synthesis, real‐time PCR, and data analysis are described previously (Kirkwood‐Johnson et al, 2021 ). To assess the impact of RDV on gene expressions in HESCA‐CSR, the Altered Level of Embryogenesis Regulator Transcript (ALERT) score was calculated, which was formulated previously (Marikawa et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a follow-up study suggested a statistically significant, albeit very small, increase in the risk for neural tube defects, dolutegravir is again listed as a preferred or alternative drug throughout pregnancy based on its availability, efficacy, and tolerance among most of the population ( 225 ). Using ESC-derived aggregates, one group found that dolutegravir disrupted gene expression of different developmental regulators, such as HOXB1 and CYP26A1 , in concentrations as low as 0.5μM ( 21 ). Further investigation of CNS-like organoids that model fetal brain development could provide a new avenue to evaluate the effects of drugs and antiviral therapies on neurodevelopment and provide novel data on the most relevant human cell types.…”
Section: Three-dimensional Culturesmentioning
confidence: 99%